Epigenetic Biomarkers of Cardiovascular Risk in Frail Patients—A Scope Review - Stanisław Wawrzyniak; Julia Cieśla; Magdalena Woś; Ewa Wołoszyn-Horák; Michał M. Masternak; Tomasz Kukulski; Ewa Stępień; Andrzej Tomasik (Current Issues in Molecular Biology)
Epigenetic biomarkers offer promising potential for early identification and risk stratification of frail individuals susceptible to adverse cardiovascular outcomes. This scope review aimed to identify and evaluate epigenetic biomarkers concurrently associated with frailty and increased cardiovascular risk, potentially facilitating more precise patient stratification and treatment decisions. A two-stage literature search was performed using PubMed, Scopus, Web of Science, and Embase databases from the year 2000 through 27 December 2024. Stage 1 identified studies reporting epigenetic biomarkers associated with frailty in blood-derived human samples. Stage 2 assessed cardiovascular relevance by screening the frailty biomarkers identified in Stage 1 for their documented association with cardiovascular diseases. Two independent reviewers conducted screening, data extraction, and risk-of-bias assessments, resolving disagreements via a third reviewer. The primary outcomes were the association of biomarkers with frailty severity and cardiovascular risk. Key epigenetic biomarkers identified included microRNAs (particularly miR-21, miR-146a, miR-451, and miR-92a) and DNA methylation markers (LINE-1 methylation, epigenetic clocks like GrimAge and DunedinPACE, and possibly novel, emerging clocks like DNAmCVDscore and the Smoking Index). Due to specificity limitations, these biomarkers are most promising when used collectively as part of multimarker panels rather than individually. Future research should validate multimarker panels, explore novel biomarkers, and assess clinical integration to optimize precision medicine in frail cardiovascular populations.